PEMANFAATAN JERAMI PADI (ORYZA SATIVA) YANG DIKONSUMSI DENGAN EM-4 TERHADAP PERTUMBUHAN DOMBA SUNGAI PUTIH JANTAN - Nanci Melisa (Universitas Sumatera Utara, 2012)
Abstract.This research aims to determine the effect of rice straw consumed awarding with the EM-4 on the feed consumption, average daily gain and feed conversion in Sungei Putih Lambs. Research carried out in the Laboratory of Animal Biologi at Faculty of Agriculture, Jalan Prof. A Sofyan No 3, University of North Sumatera, Medan, starting August 2011 to January 2012. The design used in this research was Latin Square Design consisting of 4 treatments with an initial body weight 12.79 kg ±0.20 kg. The treatment consists of P0 (concentrate +rice straw without the EM-4), P1 (concentrate+rice straw +2cc EM-4), P2 (concentrate+rice straw +4cc EM-4), P3 (concentrate+rice straw +6cc EM-4). The results showed that the Utilization of Rice Straw (Oriza sativa) are consumed with the EM-4 on The Growth Sungei Putih Lambs of feed consumption (g/head/day) 643.11; 719.18; 696.57 and 671.89, respectively. The average daily gain (g/head/day) 25,42; 40.48; 31.25 and 30.42 respectively. feed conversion rate (FCR) 25.94; 18.00; 23.99 and 22.97 respectively. Statistically shows that the utilization of the rice straw consumed with the EM-4 is not significantly different (P>0.05) on feed intake, average daily gain and feed conversion of sungei putih lambs. The conclusion of this research that the utilization of Rice Straw (Oriza sativa) with various levels EM-4 not significant influence on feed intake, body weight gain and feed conversion rate (FCR) of sungei putih lambs. Keywords: Effective Microorganisms-4 (EM-4), Rice Straw, Performance, Sungei Putih Lambs.